Buffer layers for Tl-2212 thin films on MgO and sapphire substrates - Speller, S; Wu, H; Grovenor, C (2003)
High quality Tl-2212 films can be readily grown on LaAlO3 substrates, but the design of complex microwave devices in these films is made more difficult by the twinning of the substrate. CeO2 buffer layers on sapphire have been demonstrated to offer excellent substrates for Tl-2212 films [1]. We have been exploring alternative architectures for buffer layers on MgO and sapphire. Epitaxial Tl-2212 superconducting thin films have been successfully grown on Gd2O3-buffered MgO substrates by sputter deposition of a Tl-free precursor followed by an ex-situ thalliation anneal. The Tl-2212 films were aligned with the c-axis normal to the film surface, and also had excellent in-plane orientation with Tl-2212 [100] aligned with the Gd2O3 and MgO [110]. The critical temperatures of the films ranged from 100-103 K and transport and inductive critical current densities of 7.5 x 10(5) A/cm(2) at 77 K have been achieved. We have also fabricated epitaxial GdAlO3 buffer layers on sapphire substrates which support epitaxial growth of Tl-2212 but with relatively poor microstructure. High quality films have been prepared on the new (La,Sr)(Al,Ta)O-3 (LSAT) substrates.